Threat Analysis of Khilafatul Muslimin’s Existence as A Radical Organization in Indonesia - Ma'ruf, Al Hadid Dwi Putera (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2024)
Khilafatul Muslimin (KM) is an organization established with the aim of founding a caliphate or khilafah, a system of governance based on an exclusive interpretation of Islamic leadership principles. This group promotes an ideology of the caliphate that contradicts Pancasila, Indonesia's foundational ideology, by advocating for governance rooted solely in Islamic law and singular Islamic leadership. It rejects Indonesia's principles of pluralism and democracy. The continuous efforts by KM to establish a caliphate pose a potential threat to Indonesia's sovereignty. This study aims to analyze the threats posed by KM and propose intelligence strategies to address their presence in society. A descriptive qualitative research method was employed, grounded in an inductive perspective. The analysis, based on Hank Prunckun's threat assessment framework, indicates that the threat posed by KM is at a medium level. Further threat analysis reveals that KM has the threat factors outlined by Kevin Riehle including intent, capability, and opportunity. These findings are supported by insights from perspective of the Terrorist Mindset developed by Randy Borum.